Prospective assessment of cytokines and regulatory proteins concentration in the tear fluid of POAG patients with various hypotensive effects after non-penetrating deep sclerectomy - J. V. Malisheva; T. N. Iureva; N. V. Volkova; J. V. Kursakova; S. I. Kolesnikov (Acta Biomedica Scientifica, 2023)
The aim. To assess the dynamics of cytokine content in tear fluid of primary openangle glaucoma (POAG) patients at various terms after non-penetrating deep sclerectomy (NPDS) in relation to the functional state of the outflow tracts.Material and methods. We carried out prospective examination of 65 patients with advanced stage of primary open-angle glaucoma after NPDS. Depending on the course of the postoperative period and the conditions for achieving the hypotensive effect of NPDS, all patients were divided into three groups: group 1 – with the optimal hypotensive effect; group 2 – with the conditional hypotensive effect; group 3 – with no hypotensive effect after NPDS. The intraocular pressure and the concentration of TGF-β, MMP-9, IL-6, IL-8, VEGF-A (121 and 165) in the tear fluid were studied using ELISA method in pre- and postoperative period. We studied the outflow tracts using optical coherence tomography and carried out ultrastructural analysis of filtering blebs tissue.Results. In group 1, the minimum initial concentrations of IL-6, IL-8 and TGF-β in the tear fluid and their moderate increase in the postoperative period; high concentrations of MMP-9 at all stages and an increase in VEGF-A by 2 months after NPDS were registered. In group 2, there was a high level of VEGF-A in the tear fluid before and 2 months after NPDS, an increase in TGF-β, IL-6 and IL-8 in the tear fluid in the early period with their suppression in the late period, as well as an increase in MMP-9 in the early postoperative period. Group 3 had maximum concentrations of TGF-β and IL-8 in the tear fluid initially and in the early postoperative period, suppression of MMP-9 in the tear fluid 2 weeks after and of VEGF-A 2 months after NPDS.Conclusion. Initially high concentrations of IL-6, IL-8, and TGF-β in the tear fluid and the suppression of MMP-9 and VEGF-A in the postoperative period contribute to the surgical failure of the NPDS.